Differentially Expressed Intrahepatic Genes Contribute to Control of Hepatitis B Virus Replication in the Inactive Carrier Phase. (2nd January 2018) - Liu, Hongyan; Li, Fahong; Zhang, Xiaoyong; Yu, Jie; Wang, Jinyu; Jia, Jia; Yu, Xueping; Shen, Zhongliang; Yuan, Zhenghong; Zhang, Xiaonan; Zhang, Zhanqing; Zhang, Xinxin; et al.
Abstract : In the present study, a number of genes were identified to be highly expressed in the inactive carrier state and may participate in the control of hepatitis B virus (HBV) replication and determine the inactive status of HBV infection via nonimmunological mechanisms. Abstract: Background: The natural history of chronic hepatitis B virus (HBV) infection was divided into 4 phases. Patients in the inactive carrier (IC) status and immune tolerant (IT) phase had normal alanine aminotransferase levels but huge different viral loads. The mechanism underlying low viral replication status in IC phase is unknown. Methods: We determined the intrahepatic transcriptomes of 83 chronic hepatitis B patients by microarray analysis of liver biopsies, and screened the effect of differentially regulated genes on HBV replication using specific small interfering RNAs in vitro. Results: The gene profile distinguishing active chronic hepatitis from IT and IC was predominantly composed of immune-related genes. The liver transcriptomes between the IT and IC phase were largely similar, and 109 expressed genes were significantly different. By performing systematic screening, 5 candidate genes including EVA1A, which were expressed at a relative higher level in IC phase than IT, were identified to regulate HBV replication and gene expression in cellular models. Conclusions: The immune-related pathways were up-regulated in the active chronic hepatitis phase but not in the IT and IC phase. A number of intrahepatic genes highly expressed in the IC phase may participate in the control of HBV replication and determine the inactive status of HBV infection.